The Use of Pre-Fabricated Composite Veneers to Enhance Esthetics - Panteqi Stela; Alushi Adem; Simeon Orges (Balkan Stomatological Society, 2017)
Background: This article is focused on the use of polymerized, prefabricated nano-hybrid-composite veneers to close diastema and to regain a vitality appearance of non vital discolored teeth. Case Reports: A 24-year old patient presented herself with a major complaint about the discoloration of her maxillary central incisors. The prefabricated composite veneers were recommended as the perfect solution in this case. Tooth shape and size was evaluated with the contour guide. Two pre-fabricated composite veneers size "M" were trimmed and cemented with the same hybrid composite resin that they were made from. A 28 year-old patient presented herself with a major complaint about her diastema. Her maxillary frontal teeth were intact. It was decided to use two veneers; size "L" and shade A2/B2 and Enamel Universal were chosen. Identical steps were followed as in clinical case 2. Conclusion: This new technique of treatment resulted to be an affordable way to regain esthetics. It is a one session treatment and requires no lab sessions, which makes it very comfortable for both dentist and patients. As with all new techniques, there is still a lot to be done, to confirm its effectiveness as a long term solution in esthetic dentistry.